From Lineage to Territory: The Making of Territorial Self-consciousness in Kaliṅga. (December 2017) - Devadevan, Manu V.
The evolution of territorial self-consciousness was among the most significant and historically far-reaching developments of the later half of the first millennium CE in the Indian subcontinent. However, discussions concerning this complex process have not had the benefit of systematic exploration. Although a handful of perspectives exist, they have been presented impressionistically in the context of debates on feudalism and state formation. In this article, this question is examined in relation to the rise of territoriality in the eastern Indian region of Kaliṅga. On the basis of the evidence occurring in inscriptions from the region, it is argued that large-scale expansion of agriculture and the spread of landed property, the prospects thus generated by the political control that could be exercised over its resources and the consolidation of such prospects at different local, supralocal and regional levels were the causes that resulted in the rise of Kaliṅga as a geopolitically self-conscious territory.